Pengungkapan Sustainability Reporting dengan Efek Profitabilitas dan Mekanisme Good Corporate Governance - Sasa S. Suratman; Mochammad Ridwan; Aliza Pravitasari Putri (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This study aims to examine the influence of profitability and good corporate governance mechanisms on sustainability reporting disclosure in State-Owned Enterprises listed on the Indonesia Stock Exchange. The research method employed in this study is multiple linear regression analysis. The population of the study consists of 677 companies, and a sample of 13 companies is selected using sampling techniques. The observation period for this study ranges from 2015 to 2019, resulting in a total of 65 data observations. The findings of the study indicate that profitability and the audit committee have a positive influence on sustainability report disclosure, while the board of commissioners does not have a significant impact on sustainability report disclosure. Collectively, profitability, the board of commissioners, and the audit committee have an influence on sustainability report disclosure in State-Owned Enterprises listed on The Indonesia Stock Exchange.